Academic Cancer Center Phase I Program Development. (17th March 2017) - Frankel, Arthur E.; Flaherty, Keith T.; Weiner, George J.; Chen, Robert; Azad, Nilofer S.; Pishvaian, Michael J.; Thompson, John A.; Taylor, Matthew H.; Mahadevan, Daruka; Lockhart, A. Craig; Vaishampayan, Ulka N.; Berlin, Jordan D.; et al.
Abstract : Multiple factors critical to the effectiveness of academic phase I cancer programs were assessed among 16 academic centers in the U.S. Successful cancer centers were defined as having broad phase I and I/II clinical trial portfolios, multiple investigator‐initiated studies, and correlative science. The most significant elements were institutional philanthropic support, experienced clinical research managers, robust institutional basic research, institutional administrative efforts to reduce bureaucratic regulatory delays, phase I navigators to inform patients and physicians of new studies, and a large cancer center patient base. New programs may benefit from a separate stand‐alone operation, but mature phase I programs work well when many of the activities are transferred to disease‐oriented teams. The metrics may be useful as a rubric for new and established academic phase I programs. Abstract : This commentary assesses the factors necessary for the effectiveness of academic phase I cancer programs. The metrics presented here may be useful as a rubric for new and established programs.